The Igarapé Weir decelerated transport of contaminated sediment in the Paraopeba River after the failure of the B1 tailings dam (Brumadinho) - Salgado Terêncio, Daniela Patrícia; Leal Pacheco, Fernando António [UNESP]; Farias do Valle Junior, Renato; Abreu Pires de Melo Silva, Maytê Maria; Tarlé Pissarra, Teresa Cristina [UNESP]; Carvalho de Melo, Marília; Valera, Carlos Alberto; Sanches Fernandes, Luís Filipe (Elsevier, 2023)
The B1 dam of Córrego do Feijão Mine, owned by Vale, S.A. mining company and located on the Ferro-Carvão stream, collapsed and injected 2.8 Mm3 of clayey, silty, and sandy iron- and manganese-rich tailings into the Paraopeba River (Minas Gerais state, Brazil). The accident occurred on 25 January 2019 and the tailings have been co-transported with coarser natural sediment since then, being partly trapped in the Igarapé Weir reservoir located on the Paraopeba River nearly 45 km downstream the injection point. The general purpose of the current study was to model suspended sediment transport in the vicinity of the Igarapé Weir aiming to assess the concomitant barrier effect imposed by this structure. Specifically, the spatial distributions of suspended clay, silt, and very fine-grained sand fractions (CSS) of sediment were mapped around the Igarapé Weir under low-flow (16 m3/s) and high-flow (5 to 10,000 years return period stream discharge; 699–2,699 m3/s) regimes, using RiverFlow2D as the modelling tool. The concentrations of the various grain materials in the upstream and downstream sectors were quantified linking the barrier effect to concentration reductions in the direction of stream flow. It was also a study goal to calculate differences of iron and manganese concentrations in the sediment + tailings mixtures along the Paraopeba River. The study results showed reductions in the CSS between 6.6% and 18%, from upstream to downstream of the Igarapé Weir, related with backwater effects, free and submerged hydraulic jumps, bank sedimentation in periods of high flow, and streambed sedimentation controlled by channel sinuosity and tailings density. These reductions were accompanied by drops in the concentrations of iron and manganese present in the clay and silt fractions, which varied between 6% and 42% under low flows and between 16% and 44% under high flows. Bank sedimentation was viewed as a potential threat to the riparian vegetation in the long-term. Dredging is the potentially most effective mitigation measure to help lead the Paraopeba River to a pre-rupture condition. The retention of sediment + tailings transported in suspension is less effective than the trapping of bedload sediment + tailings behind the Igarapé weir. The efficacy of sediment trapping is expected to be larger for natural sediment because it is much coarser than the tailings. In that context, the simulations revealed for the low-flow period that 33.6% of the sediment deposition comprised suspended transport of natural sediment (thus, was comprised 66.4% of bedload transport), this proportion rose to 86.9% for mixtures of natural sediment + tailings, a result that did not differ much for the high-flow periods.
Keywords: Hydrodynamic modelling; Metal contamination; Ratio concentration analysis; RiverFlow2D; Sediment transport; Tailings dam break